2020
DOI: 10.1038/s41597-020-00743-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly accurate long-read HiFi sequencing data for five complex genomes

Abstract: The PacBio® HiFi sequencing method yields highly accurate long-read sequencing datasets with read lengths averaging 10–25 kb and accuracies greater than 99.5%. These accurate long reads can be used to improve results for complex applications such as single nucleotide and structural variant detection, genome assembly, assembly of difficult polyploid or highly repetitive genomes, and assembly of metagenomes. Currently, there is a need for sample data sets to both evaluate the benefits of these long accurate read… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(119 citation statements)
references
References 39 publications
1
106
0
Order By: Relevance
“…Single molecule, real-time (SMRT) sequencing developed by PacBio (California, United States) detects differently labelled dNTPs as they are incorporated into a DNA strand ( Eid et al, 2009 ). The read length when using SMRT sequencing is primarily limited by the longevity of the DNA polymerase, with average read lengths of >20 kb now possible ( Hon et al, 2020 ). To achieve high accuracy, DNA molecules are circularised prior to sequencing, allowing circular consensus sequencing (CCS), where the polymerase progresses around the circularised template multiple times.…”
Section: Sequencing Technologies For Detecting Rna Isoformsmentioning
confidence: 99%
“…Single molecule, real-time (SMRT) sequencing developed by PacBio (California, United States) detects differently labelled dNTPs as they are incorporated into a DNA strand ( Eid et al, 2009 ). The read length when using SMRT sequencing is primarily limited by the longevity of the DNA polymerase, with average read lengths of >20 kb now possible ( Hon et al, 2020 ). To achieve high accuracy, DNA molecules are circularised prior to sequencing, allowing circular consensus sequencing (CCS), where the polymerase progresses around the circularised template multiple times.…”
Section: Sequencing Technologies For Detecting Rna Isoformsmentioning
confidence: 99%
“…Comparing to previous studies, Latorre-Perez et al 2020 found that available MinION assembly algorithms were able to accurately assemble simple metagenomes of mock microbial communities that were subjected to deep sequencing (14-16 giga basepairs per sample that were subsampled 3 and 6 Gbp) 55 , the present study illustrates that there are still significant shortcomings in the application of these pipelines to more complex environmental metagenomes. While it is possible that the decreased error rate 56 provided by PacBio HiFi sequencing might improve assembly, we suspect that sequencing depth is a larger driver of assembly error rate. Additionally, we note that we did not explore the possibility of error correction in the long-read assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…The raw sequencing data were processed using the SMRTlink ( Hon et al, 2020 ) software with the parameters: --min_passes 3; --min_length 50; --max_length 15,000. The high-quality sequencing reads produced by a single molecule in the sequencing process are called polymerase read, and the polymerase reads remove the sequencing adapters to form subreads.…”
Section: Methodsmentioning
confidence: 99%